Chorioamnionitis and Lung Injury in Preterm Newborns - Gustavo Rocha (Critical Care Research and Practice)
There is a strong evidence that histologic chorioamnionitis is associated with a reduction of incidence and severity of respiratory distress syndrome (RDS). Short-term maturational effects on the lungs of extremely premature infants seem to be, however, accompanied by a greater susceptibility of the lung, eventually contributing to an increased risk of bronchopulmonary dysplasia (BPD). Genetic susceptibility to BPD is an evolving area of research and several studies have directly related the risk of BPD to genomic variants. There is a substantial heterogeneity across the studies in the magnitude of the association between chorioamnionitis and BPD, and whether or not the association is statistically significant. Considerable variation is largely dependent on differences of inclusion and exclusion criteria, as well as on clinical and histopathological definitions. The presence of significant publication bias may exaggerate the magnitude of the association. Controlling for publication bias may conduct to adjusted results that are no longer significant. Recent studies generally seem to confirm the effect of chorioamnionitis on RDS incidence, while no effect on BPD is seen. Recent data suggest susceptibility for subsequent asthma to be increased on long-term followup. Additional research on this field is needed.